Application of C-PBL (Context and Problem Based Learning) on Temperature and Heat Materials to Transform Students' Mental Models - Sabarrini, Mutiara Aulia; Ramlan Ramalis, Taufik; Mustika Sari, Ika (Physics Education Research Journal, 2024)
This research aims to determine students' conceptual understanding through the C-PBL (Context- and Problem-Based Learning) learning model. The method used was quasi-experimental with a posttest-only control group design. The population in this study were all class XI students in one of the high schools in Bandung. The sampling technique uses cluster random sampling. The samples used were class XI MIPA 1 as the control class and class XI MIPA 3 as the experimental class. Both classes were given a final test (posttest) after applying the C-PBL model in the experimental class and the discovery learning model in the control class. The research results showed that there were differences in students' conceptual understanding in the experimental class and the control class. Analysis of research results using hypothesis testing of the difference between the experimental and control classes averages using the t-test. The t-test was conducted using Microsoft Excel, and the sig results were obtained. (2– tailed) of 0.00. These results show that the C-PBL model significantly influences the mental physics model.